DAMPAK INTERAKSI ASIMETRI INFORMASI TERHADAP UKURAN PERUSAHAAN, LEVERAGE DAN KOMPENSASI PADA MANAJEMEN LABA - Sutapa, I Nyoman; Dharma Suputra, I Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
The present study is aimed at providing empirical evidence on the impact of information asymmetry on the correlation among size of company, leverage and compensation of profit management. The population included in this study was manufacturer listed in Indonesian stock exchange from 2012 to 2014 period with total sample of 189 companies. The sample collection method used was purposive sampling and the testing measurement used was moderated regression analysis. The result of this study proves that information asymmetry can moderate between the impact of size of company on profit management, the higher the information asymmetry, the higher the profit management through a company measurement with the interaction of information asymmetry on profit management. However, information  asymmetry is not able to moderate the impact of leverage on profit management as well as the impact of compensation on profit management.
Keywords: Earnings management, firm size, leverage, compensation, information asymmetry